The future of statehood in East Africa - Shuriye, Abdi Omar; Ajala, Mosud T. (Canadian Center of Science and Education, 2016)
With the deterioration of political and security situations in Somalia and Kenya’s involvement in the war against al-shabaab as well as its political miscalculation and the lack of exit plan, add to this, the fading democratic conditions in Eritrea, accompanied by the political uncertainties in Ethiopia, since the demise Meles Zenawi Asres and the extermination of the opponents, as shown in last general election, as well as the one-man-show political scenario in Uganda and the likely disintegration of Tanzania into Zanzibar and Tanganyika, indicated by the ongoing elections; the political future of East African governments is predictably taking erroneous turns. It seems therefore, God forbids, there is a political catastrophe in the making as far as the state as an authoritative institution is concerned in East Africa. One observes that the social fabric of these states, take Kenya, which used to be a solid in its social and political values, as an example, is drastically changing into a pattern-of-Somali-like tribal syndrome. The expiration of the government institutions, civil societies, law and order in Eritrea, the austere political future of Djibouti, the irrepressible and incurable wounds of Burundi and Rwanda are shrilling pointers of such fear. Not to forget, the strained Muslim-Christian relations, which is now deeply rooted in these communities and states, the thick-headedness of most East Africa’s political leaders and the rapid increase of the youth population as well as the proxy war in business between China and the West on the region. These factors are the core indicators of the future of state and strong government in East Africa. The study covers several nations in East Africa including Burundi, Djibouti, Eritrea, Ethiopia, Kenya, Rwanda, Somalia, Tanzania, and Uganda.